Penyuluhan Keseimbangan untuk Atlet Tenis Lapangan dengan Program Ankle Strategy Exercise - Sany Ayu Kurniawati; Arif Pristianto; Siti Soekiswati (Jurnal Health Sains, 2021)
Balance is a person's ability to control the position of his body against the base of the footing. Balance is a complex interaction and interaction of sensory systems (vestibular, visual, and somatosensory including propioceptors) and musculoskeletal (muscles, joints, and other soft tissues) that are regulated in the brain (motor control, sensory, basal ganglia, cerebellum and associate areas). Reduced ability to maintain balance results in an increased risk of falls. This ankle strategy exercise is used to train balance in field tennis athletes. This extension aims to increase knowledge to coaches and athletes about balance and exercises used to improve balance. The implementation of this extension activity, carried out by the method of presentation and discussion. There are 2 methods given, namely the presentation method explaining the content of the extension material and the demonstration method to provide examples of exercises that have been described. The result of this counseling is an increased knowledge and understanding from coaches and athletes about the material and a reduced risk ofinjury